Boron recovery from montmorillonite clay waste using sequential leaching followed by cooling crystallization techniques - Çelebi, E. Ender; Öncel, Mehmet Salim (Springer Science and Business Media Deutschland GmbH, 2021)
A four-stage sequential leaching (SL) and subsequently cooling crystallization (CC) techniques have been implemented for the recovery of boron from the clay waste (CW) induced by the borax derivatives production facility located in Kırka district of Eskişehir province, NW of Turkey. Optimum experimental solid-liquid ratio and agitation time for SL tests were determined by preliminary experiments. In the first leaching stage, approximately 85% of boron in the CW was transited to the leachate. A logarithmic decrease in the boron transition efficiency was obtained as a function of stages. After four-stage SL procedure, CC procedure was carried out with the last leachate at 4.0 °C ±0.3 stabilized refrigerator. Approximately 77% of dissolved boron in the last leachate was crystallized by CC as high purity borax crystals. Mineralogical, chemical, and physical definitions of the crystals were determined by X-ray diffraction (XRD), instrumental element analysis following microwave digestion, and scanning electron microscopy (SEM) procedures, respectively. As a result, sequential leaching followed by cooling crystallization system was determined as an effective methodology for the recovery of boron from the CW as high purity borax form. © 2021 Elsevier B.V., All rights reserved.
Keywords: Borax deposits; Boron recovery; Clay waste; Cooling crystallization; Sequential leaching